Tinjauan Kritis Terhadap Deviasi Akad Murabahah Dalam Aplikasinya Pada Perbankan Syari’ah - Syu'aibun Syu'aibun (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
This article explains that the murabahah contract applications on Shariah banking has some deviation (deviation), including murabahah financing practices that often occur in Shariah banks are not purely as a seller of goods as in the trade industry that sells goods directly to the buyer, because at large banks (Ba'i) do not have the goods. The role of banks as ba'i in murabahah financing is more aptly described as a financier and not a seller of goods, because the bank does not hold the goods, nor to take risks with it. Banks work as ba'i almost everything is only associated with the handling of documents. Mark-up imposed on murabahah contract is basically not much different from the system of interest. On the basis of these deviations, then the application syari'ah murabahah in the banking system cannot be expressed fully in accordance with the principles of shariah economy.